USING “TEXT TWIST 2” GAMES TO INCREASE STUDENTS VOCABULARY PRACTICE IN STUDY ENGLISH (SURVEY AT THE FIRST GRADE OF SMPN 11 BATAM) - Sri Sugiharti (Universitas Riau Kepulauan, 2016)
This study is to analyze the effect using “Text Twist 2” games as media to increase students vocabulary practice in study English. a learner to facing world challenge must prepare and ready themselves, to all pressure the students must meet this challenge controlled with English language. Many method that teacher show to make students understood about English language. To increase students abilities in speaking, reading, listening, and writing, teacher must make their skill can be productive and using in social. Reading that also as the way for vocabularies building.Research is the next objective from the writer as the way to find out the effect from this method. In this case, the writer choose Action Research and to try inprove this research with games. The result is Students can find out more vocabularies as modal to be ready in speaking English used “Text Twist 2” games can increase the students’ vocabulary practice in study English. The students’ average score is 74.42. It fulfills the criteria of success which is determined 70.00 or more. Keywords: text, increase, vocabulary, games and Vocabulary